1997
DOI: 10.1111/j.1095-8649.1997.tb01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and predator effects on morphology and physiology of crucian carp in nature and in the laboratory

Abstract: Crucian carp Carassius carassius show great phenotypic plasticity in individual morphology and physiology, and strong variation in population density in different fish communities. Small fish with shallow bodies and large heads are typical in overcrowded monospecific fish communities in small ponds, whereas deep-bodied, large fish are found in larger, multispecies lakes. Crucian carp are especially vulnerable to predation by piscivorous fish and their greater relative body depth in multispecies fish communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
98
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 31 publications
10
98
1
1
Order By: Relevance
“…Firstly, the classical alarm pheromones triggering behavioural responses are not the ones possessing the primer pheromone effect (e.g., Karlson and Lüscher 1959;Wilson and Bossert 1963), meaning that they are not the causative agents for inducing morphological changes in crucian carp. Secondly, permanent presence of alarm signals do not result in increased body depth through indirect behavioural means, causing decreased activity, energy allocation and an higher overall growth, as suggested by some authors (e.g., Holopainen et al 1997a;Vøllestad et al 2004;Andersson et al 2006;Johansson and Andersson 2009). Our results may, on the other hand, explain the lack of morphological responses from the "scratching with a knife" injury method by Brönmark and Pettersson (1994), because non-soluble tissue may not have been released with that method.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Firstly, the classical alarm pheromones triggering behavioural responses are not the ones possessing the primer pheromone effect (e.g., Karlson and Lüscher 1959;Wilson and Bossert 1963), meaning that they are not the causative agents for inducing morphological changes in crucian carp. Secondly, permanent presence of alarm signals do not result in increased body depth through indirect behavioural means, causing decreased activity, energy allocation and an higher overall growth, as suggested by some authors (e.g., Holopainen et al 1997a;Vøllestad et al 2004;Andersson et al 2006;Johansson and Andersson 2009). Our results may, on the other hand, explain the lack of morphological responses from the "scratching with a knife" injury method by Brönmark and Pettersson (1994), because non-soluble tissue may not have been released with that method.…”
Section: Discussioncontrasting
confidence: 38%
“…3), when the fish were released into ponds at low densities with abundant natural food, BDI and CF showed a linear relationship. However, in neither case any signs of increased growth resulting from presence of alarm signals were noted, as proposed by Holopainen et al (1997a). On the contrary, in both the environments we found that crucian carp exposed to chemical alarm signals grew less when compared to control fish.…”
Section: Discussionmentioning
confidence: 34%
“…The larger size of roach water fish might thus be a response to a perceived amount of competition. In crucian carp for example both predation risk and intraspecific competition has been shown to influence morphology (Holopainen et al 1997). A similar pattern has been described in wood frog tadpoles (Rana sylvatica) which developed larger bodies and smaller tails, both in the presence of conspecific and heterospecific competitors (Relyea 2002a).…”
Section: Discussionmentioning
confidence: 58%
“…4 Differentiation of the three treatment groups of adult sticklebacks along the first two CV axes. Deformation grid with displacement vectors for CV1 (a) and CV2 (b) demonstrated in other animal species (e.g., Brönmark and Miner 1992;Holopainen et al 1997;Lass and Spaak 2003;Hettyey et al 2010). Body shape, spine length, condition factor and standard length of juveniles and adults were quantified after rearing full-sibs Eight principal components comprising most explanatory power ([2%) were tested Significant differences (P \ 0.05) are given in bold under regular perch water (predator-treatment), roach water (non-predator-treatment, fish control) and tap water treatment (treatment control).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation